ANALYSIS OF PATHOGENIC IUTA GENE MARKERS IN ESCHERICHIA COLI CAUSES OF COLLIBACILLOSIS IN FREE-RANGE CHICKEN - Marhendra, Kadek Satria Adi; Mahardika, I Gusti Ngurah Kade; Besung, I Nengah Kerta; Suarjana, I Gusti Ketut (Buletin Veteriner Udayana, 2021)
Colibacillosis is an infectious disease in chickens caused by Avian Pathogenic Escherichia coli (APEC). The ability of APEC to cause disease depends on many pathogenic factors, one of which is the iutA pathogenic gene. This study was purposed to determine the DNA sequence of the APEC iutA gene in Bali and its kinship with the iutA gene from other countries. Two APEC isolates from free-range chicken in Tabanan dan Badung has been used. The isolates have been purified and were available at the Bacteriology Laboratory of Veterinary Medicine Faculty, Udayana University. Chelex 10% was used for DNA isolation. DNA amplification using published DNA primer has been conducted with the polymerase chain reaction (PCR) method. The PCR product was sequenced at Malaysia, First Base Laboratories using Sanger’s Dideoxy Nucleotide Termination method. The i utA gene of both isolates can be analyzed and have 250 bp in length. Both were 100% homologous. A phylogenic test using 58 DNA sequences of i utA gene from Escherichia coli and other bacteria in the world was conducted in MEGA 5.2. All data have 43 polymorphic sites of nucleotide acid and 13 polymorphic sites of amino acid. The iutA gene from Bali is in one group, with the iutA gene from Brazil (KP657535) in 2011, Germany (LT599825) in 2016, and China (CP033635) in 2016. This gene can be used as a pathogenic marker of APEC in Indonesia.